Two cases of resected gallbladder carcinosarcoma with a contrasting course. (March 2022) - Kato, Toru; Kimura, Yasutoshi; Kubo, Tomohiro; Murota, Ayako; Hasegawa, Tadashi; Takemasa, Ichiro
Abstract: Introduction: Carcinosarcoma of the gallbladder is a rare tumor with both carcinoma and sarcoma components. Case presentation: In this paper, we report two cases. The first case is of a man in his 60s who was preoperatively diagnosed with gallbladder carcinosarcoma and has achieved 6 years and 6 months survival through aggressive surgical treatment. The second case is of a woman in her 70s who was diagnosed with locally advanced gallbladder cancer; she underwent multidisciplinary treatment for the same, but died 8 months after the surgery. While the primary disorder was the same in both cases, the clinical courses contrasted sharply. Discussion: There is no established chemotherapy or radiation therapy for gallbladder carcinosarcoma, and the only curative treatment is surgery. However, it has a very poor prognosis. Conclusion: Carcinosarcoma of the gallbladder may progress very rapidly, and the treatment management should be carefully decided. Highlights: Carcinosarcoma has both carcinoma and sarcoma components; it rarely occurs in the gallbladder. We present two resected cases of highly advanced gallbladder carcinosarcoma. We performed the first pre- and postoperative chemotherapy for gallbladder carcinosarcoma. One case has the longest post-resection relapse free survival.